Assessing the Efficacy of Restricting Access to Barbecue Charcoal for Suicide Prevention in Taiwan: A Community-Based Intervention Trial. - Ying-Yeh Chen; Feng Chen; Shu-Sen Chang; Jacky Wong; Paul S F Yip (PLoS ONE, 2015)
Charcoal-burning suicide has recently been spreading to many Asian countries. There have also been several cases involving this new method of suicide in Western countries. Restricting access to suicide means is one of the few suicide-prevention measures that have been supported by empirical evidence. The current study aims to assess the effectiveness of a community intervention program that restricts access to charcoal to prevent suicide in Taiwan.A quasi-experimental design is used to compare method-specific (charcoal-burning suicide, non-charcoal-burning suicide) and overall suicide rates in New Taipei City (the intervention site, with a population of 3.9 million) with two other cities (Taipei City and Kaohsiung City, the control sites, each with 2.7 million residents) before (Jan 1st 2009- April 30th 2012) and after (May 1st 2012-Dec. 31st 2013) the initiation of a charcoal-restriction program on May 1st 2012. The program mandates the removal of barbecue charcoal from open shelves to locked storage in major retail stores in New Taipei City. No such restriction measure was implemented in the two control sites. Generalized linear regression models incorporating secular trends were used to compare the changes in method-specific and overall suicide rates before and after the initiation of the restriction measure. A simulation approach was used to estimate the number of lives saved by the intervention. Compared with the pre-intervention period, the estimated rate reduction of charcoal-burning suicide in New Taipei City was 37% (95% CI: 17%, 50%) after the intervention. Taking secular trends into account, the reduction was 30% (95% CI: 14%, 44%). No compensatory rise in non-charcoal-burning suicide was observed in New Taipei City. No significant reduction in charcoal-burning suicide was observed in the other two control sites. The simulation approach estimated that 91 (95%CI [55, 128]) lives in New Taipei City were saved during the 20 months of the intervention.Our results demonstrate that the charcoal-restriction program reduced method-specific and overall suicides. This study provides strong empirical evidence that restricting the accessibility of common lethal methods of suicide can effectively reduce suicide rates.